P503 Inflammatory bowel disease video-consulting: a satisfaction survey during the second wave of Covid-19 pandemics. (27th May 2021) - Todeschini, A
Abstract: Background: During the SARS-CoV-2 pandemic there was a substantial change in providing medical care. National and international statements recommended avoiding face-to-face visit for treatment of patients especially for chronic disease. Also lockdown and social distancing cause a lot of concern among patients, which prefer avoid hospital facilities due to fear of contracting COVID-19. For these reason there was a reorganization of inflammatory bowel disease follow-up visit shifting from traditional visit to telemedicine whereas it' was possible. Our survey aimed to evaluated satisfaction about follow up video-consulting in IBD patients. Methods: From September to December 2020, 75 video-consults were made as follow up in patients with IBD. Video-consult wasn't performed as first visit nor in patients with new clinical issue. Every consult lasted about 15 minutes. At the end of the visit, a questionnaire of satisfaction was e-mailed to each patient. This questionnaire evaluated several items: satisfaction, difficulty of connection, opportunity to repeat the video-consult even in post-Covid-19 era, safety compared to face-to-face visit, level of concern about Covid-19 disease and fear of in-hospital transmission Results: 70% of the patients indicated an high video-consult rating and in most of cases (88%) there were no connection problems. The majority (88%) would like to repeat the tele-visit even in the post-Covid 19 era (77%). Video-consult seemed to be perceived as safer than face-to-face visit even if, in case of urgent consultation, it was preferred a traditional visit. Moreover, Covid-19 infection and fear of in-hospital trasmission was a great concern in the 73% and 58% of the patients respectively. Conclusion: In our survey, outpatients reported a very high degree of satisfaction with video consultations. It was an easy and safe tool that may become an integral part of clinical practice in the future.